2011
DOI: 10.1016/s1880-4276(11)80042-6
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Singapore and Malaysia: Current Trends and Future Prospects

Abstract: Atrial fibrillation (AF) imposes substantial burdens of morbidity and impaired health‐related quality of life, and significantly increases sufferers' risk of having a cardiovascular event, in particular a stroke. Prevalence of AF in Asia and the associated healthcare costs are likely to have been underestimated and are expected to increase due to greater awareness, population ageing and increasing prevalence of associated risk factors and comorbidities. The AF management paradigm is shifting from a conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…17 Despite the fact that AF ablation is a standard treatment, there were only a few studies reported the success rate in the Asian population and even less with Southeast Asian region with only two reports from Singapore and Malaysia. 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Despite the fact that AF ablation is a standard treatment, there were only a few studies reported the success rate in the Asian population and even less with Southeast Asian region with only two reports from Singapore and Malaysia. 18…”
Section: Discussionmentioning
confidence: 99%
“…17 Despite the fact that AF ablation is a standard treatment, there were only a few studies reported the success rate in the Asian population and even less with Southeast Asian region with only two reports from Singapore and Malaysia. 18 Asian ethnicity also tends to have lower body weight and BMI compared to other ethnicity. A higher BMI is associated with a lower chance of freedom of AF.…”
Section: Patient Factorsmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrythmia and is associated with costly cardiovascular morbidity such as stroke and heart failure [6][7][8]. The need for long term adherence to complex therapies, fluctuating symptoms and increased risk of adverse outcomes make AF a challenging condition for patients to manage [9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the sporadic and highly variable nature of disease, traditional healthcare models of pre-scheduled appointments with health providers may be poorly suited to meet the unpredictable and potentially urgent needs of AF patients [10]. With greater awareness, ageing populations and the rise in predisposing risk factors such as hypertension and diabetes mellitus, the prevalence of AF and its associated healthcare costs are expected to increase substantially [6,7]. This highlights the importance of adopting new strategies to optimize the management of this growing epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, this number has increased over recent years due to population ageing, increasing prevalence of comorbidities (diabetes, hypertension, ischaemic heart disease) and increased awareness and diagnosis of AF. 6 AF affects the quality of life. It increases the risk of stroke and heart failure; and overall mortality rate is approximately double compared to patients in normal sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%